Health effects of airborne particulate matter related to traffic in Urmia, north-west Iran - Amir Mohammadi (Journal of Air Pollution and Health, 2019)
Introduction: This study aimed to evaluate exposure to PM10 related to traffic and drying Lake Urmia and its effects on human health in north-west of Iran. Materials and methods: Sampling and analysis was done during 2015 to 2016 using AirQ 2.2.3. Results: The annual mean of PM10 concentrations were 106 μg/m3, which was too higher than 20 μg/m3 recommended by WHO guideline. The maximum seasonal mean concentration of PM10 was observed in winter (138 μg/m3). Attributable proportion (AP) due to exposure to PM10 were estimated 5.487% (95%CI: 3.726-7.185%) of non-accidental mortality cases, 8.011% (95%CI; 4.615-11.174%) of cardiovascular mortality, and 11.174% (95%CI; 4.615-16.215%) of respiratory mortality, for Urmia inhabitants. With every 10 μg/m3 increase in PM10 concentrations, relative risk (RR) for total mortality increased by 0.6%. Conclusion: The total cases numbers for hospital admission due to cardiovascular and respiratory diseases in central RR were 257 and 666 cases, respectively. Since incineration fossil fuel, the salty dust storms caused by climate change and drying Urmia Lake is natural, therefore, increasing green space and extensive activities such as desertification are need to control this phenomenon that is extremely challenging.